Low expression of acyl-CoA thioesterase 13 is associated with poor prognosis in ovarian serous cystadenocarcinoma - Lv, Xiaofeng; Wang, Weijiao; Liu, Xiaoyu; Liu, Yuhuan; Guo, Lili; Wang, Changyu (Frontiers in Genetics, 2023)
Objective: Acyl-CoA thioesterase 13 (ACOT13) encodes a member of the thioesterase superfamily. It has not been reported in ovarian cancer. This research aimed at evaluating the expression and prognostic value of ACOT13 in ovarian serous cystadenocarcinoma (OSC).Methods: We extracted and analyzed TCGA, GEPIA, THPA, GTEx, miRWalk and GDSC databases to investigate the potential carcinogenic mechanism of ACOT13 in OSC, including the correlation of ACOT13 with prognosis, immune checkpoint, tumor mutational burden (TMB), and 50% inhibition concentration (IC50) score. The incidence of endpoint events was compared with Kaplan-Meier survival analysis. Independent prognostic factors for OSC were evaluated with univariate and multivariate Cox regression analyses, and a nomogram was established.Results: The expression of ACOT13 was increased in OSC and correlated with tumor stage, with higher expression in stages I and II than in stages III and IV. Besides, it was observed that low expression of ACOT13 is correlated with poor overall survival (OS), progression-free survival (PFS), and disease-specific survival (DSS) in patients with OSC. There was a positive correlation between ACOT13 expression and immune checkpoint sialic acid-binding Ig-like lectin (SIGLEC) 15 and TMB. Patients with low ACOT13 expression had higher cisplatin IC50 scores. Conclusion: ACOT13 is an independent prognostic factor and a promising clinical target for OSC. In the future, the carcinogenic mechanism and clinical application value of ACOT13 in ovarian cancer need to be further studied.